2021
DOI: 10.1002/cplu.202100191
|View full text |Cite
|
Sign up to set email alerts
|

Germanium‐Based Halide Perovskites: Materials, Properties, and Applications

Abstract: Perovskites are attracting an increasing interest in the wide community of photovoltaics, optoelectronic, and detection, traditionally relying on lead-based systems. This Minireview provides an overview of the current status of experimental and computational results available on Ge-containing 3D and lowdimensional halide perovskites. While stability issues analogous to those of tin-based materials are present, some strategies to afford this problem in Ge metal halide perovskites (MHPs) for photovoltaics have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 51 publications
(189 reference statements)
0
64
0
Order By: Relevance
“…31 Because of their high moisture stability and strong light absorption, lead-free copper (Cu)-based perovskites have piqued the interest of researchers. Vargas et al reported 2D double perovskite Cs 4 CuSb 2 Cl 12 with a reduced bandgap of 1 eV due to the presence of an unpaired electron in 3d 9 -configurated Cu 2+ where overlapping of Cu-3d orbitals with Cl and Sb orbitals leads to valence band broadening and bandgap narrowing. 32 Copper doping in double perovskites has previously been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Because of their high moisture stability and strong light absorption, lead-free copper (Cu)-based perovskites have piqued the interest of researchers. Vargas et al reported 2D double perovskite Cs 4 CuSb 2 Cl 12 with a reduced bandgap of 1 eV due to the presence of an unpaired electron in 3d 9 -configurated Cu 2+ where overlapping of Cu-3d orbitals with Cl and Sb orbitals leads to valence band broadening and bandgap narrowing. 32 Copper doping in double perovskites has previously been studied.…”
Section: Introductionmentioning
confidence: 99%
“…1 Lead-free perovskites are one tool for overcoming the stability and toxicity issues associated with Pb 2+ by substituting other divalent metals such as Sn 2+ 2–6 and Ge 2+ . 7–11 The perovskite structure with the general formula A 3 B 2 X 9 , where B is a trivalent metal such as Bi 3+ 12–15 or Sb 3+ , 16–19 has different polymorphs with varying dimensions depending on the nature of the B–X sublattice link. The zero-dimensional (0D) hexagonal crystal structure is the most frequently reported polymorph for A 3 B 2 X 9 perovskites where isolated [B 2 X 9 ] 3− dimers synthesized from octahedral interstitial sites include ordered hexagonal close-packed A 3 X 9 with B cations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because the metal central atom plays a crucial role on the electronic structure of MHPs, we were interested in comparing the HP effects for a similar system but containing a different metal, namely germanium. We recently started to investigate the structure-property correlation in Ge-based 2D perovskites with the aim of understanding how the replacement of this ion for lead affects the structural, electronic, and optical properties, also considering the significant environmental problem raised by lead use and the necessity of finding possible lead-free alternatives ( Malavasi et al., 2021a , 2021b ). To the best of our knowledge, the present paper not only provides the first high-pressure experimental work on DA 2 PbI 4 and DA 2 GeI 4 , the latter being a novel perovskite, but also represents the only available work of the pressure response of a Ge-based 2D MHPs.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 However, the resulting Sn-and Ge-based halide perovskites suffer a more severe stability issue because the Sn 2+ and Ge 2+ cations with high-lying s 2 states tend to further lose electrons for the higher oxidation state of +4. 20,21 On the other hand, the group V elements Bi and Sb have also been used to replace the Pb, yielding layered perovskites and sometimes nonperovskites with the chemical formula of A 3 B 2 X 9 for the charge balance. 22,23 These Bi-and Sb-based halides generally exhibit superior stability because it is relatively difficult to remove the deep-lying s 2 states of Bi and Sb for the higher oxidation state of +5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The most obvious candidates for replacing the Pb in the lead halide perovskites are the group IV elements Sn and Ge, because their similar ionic radii and s 2 p 0 electronic configurations can maintain the three-dimensional (3D) perovskite structure and electronic structure similar to those of lead halide perovskites, respectively. , However, the resulting Sn- and Ge-based halide perovskites suffer a more severe stability issue because the Sn 2+ and Ge 2+ cations with high-lying s 2 states tend to further lose electrons for the higher oxidation state of +4. , On the other hand, the group V elements Bi and Sb have also been used to replace the Pb, yielding layered perovskites and sometimes nonperovskites with the chemical formula of A 3 B 2 X 9 for the charge balance. , These Bi- and Sb-based halides generally exhibit superior stability because it is relatively difficult to remove the deep-lying s states of Bi and Sb for the higher oxidation state of +5. However, the lower-dimensional A 3 B 2 X 9 structures lead to lower electronic dimensionalities and thus larger band gaps, larger effective carrier masses, and deteriorative defect properties .…”
Section: Introductionmentioning
confidence: 99%